INTERACTIVE-LECTURE-DEMONSTRATIONS AND GUIDED-REVERSE JIGSAW INSTRUCTIONAL STRATEGIES, AND SECONDARY SCHOOL STUDENTS’ LEARNING OUTCOMES IN CONCEPTS OF LIGHT IN PHYSICS IN OYO STATE, NIGERIA (2023)
Physics, a unifying subject for most science-related disciplines is important for technological advancement. Reports have shown that academic achievement in and attitude to physics particularly in concepts of light among senior secondary students in Oyo State are poor. Previous studies have focused largely on student-related factors that influence learning outcomes in physics, with little attention paid to student-centred strategies such as Interactive-lecture-demonstrations Strategy (IldsS) and Guidedreverse Jigsaw Strategy (GrJS). This study therefore, was carried out to determine the effects of (IldsS) and (GrJS) on students’ learning outcomes (achievement in and attitude to) in concepts of light in physics. It also examined the moderating effects of gender and students’ commitments to physics. John Dewey’s Constructivist Theory of Interaction and Albert Bandura’s Social Cognitive Theory underpinned the study. The pretest-posttest control group quasiexperimental design with a 3x2x2 factorial matrix was adopted. One Local Government Area (LGA) was randomly selected from each of the three existing senatorial districts in Oyo State. Three schools were purposively selected from each LGA based on availability of qualified physics teachers and functional laboratory. Intact classes of Senior School II students from each school were randomly assigned to IldsS (83), GrJS (126) and control (105) groups. The instruments used were Physics Achievement Test (r=0.78), Students’ Commitment to Physics Scale (r=0.80), Students’ Attitude Questionnaire (r=0.87) and instructional guides. The treatment lasted 10 weeks. The data were analysed using descriptive statistics, Analysis of covariance and Bonferroni Post-hoc test at 0.05 level of significance. The participants’ age was 15.30±2.50 years and 52.9% were female. The participants’ commitment to physics (45.2%) was low. Treatment had a significant main effect on students’ achievement in concepts of light in physics (F(2, 312) = 53.95; partial η2 = 0.26). The participants in IldsS had the highest post-achievement mean score (11.89), followed by those in GrJS (11.82) and the control (8.55) groups. There was a significant main effect of treatment on students’ attitude to physics (F(2, 312) = 44.28; partial η2 = 0.23). The participants in IldsS had the highest post-attitude mean score (50.70), followed by those in GrJS (45.12) and control (42.30) groups. There was a significant main effect of students’ commitment to physics on achievement (F(1, 313) = 6.54; partial η2 = 0.02), but not on attitude to concepts of light. The participants in high commitment group obtained a higher post mean score (11.13) than their counterparts with low (10.38) commitment group. The main effects of gender were not significant on students’ achievement in and attitude to concepts of light. The two-way and threeway interaction effects on achievement in and attitude to concepts of light were not significant. Interactive-lecture-demonstrations and guided-reverse jigsaw instructional strategies improved students’ achievement in and attitude to concepts of light in physics in Oyo State, Nigeria with emphasis on students’ commitment to physics. Both strategies should be adopted by physics teachers.